Challenges of Educational Development in Nigeria: Issues of Chemical Sciences - Hashimi, M. Adejumoke (NIU Journal of Social Sciences, 2021)
A wealth of research has revealed that scientific skill is crucial for national development and material well-being of any country. While lack of scientific knowledge is often a critical limitation to economic progress, hence, the importance of science in Nigeria Educational system cannot be over emphasized. So there is a need to improve on science subjects/courses in our schools and institutions if the country is to meet the rising expectation of people. This paper, discusses among other things the place of science in Nigeria Educational system as stated in the National Policy of Education. It brings into fore the importance of science programmes in the National development. However, the paper focuses more importantly on chemical sciences, because of the role it plays among the basic sciences, afterall, after God, the power of creation is given to chemists. The paper discusses further the challenges that are facing the effective teaching and learning chemistry in Nigerian schools. At the tail end of the paper it proffers likely solutions. Finally, the paper is ended with suggestions, recommendations and conclusion. It is important that government at all levels should fund education and increase annual budgetary allocation to minimum recommendation of United Nations Educational, scientific and cultural education (UNESCO) which is 26%. Keywords: Science and Technology, Chemistry, Educational Development, Nigerian Schools.